Aqueous one-pot synthesis of epoxy-functional diblock copolymer worms from a single monomer: new anisotropic scaffolds for potential charge storage applications. Issue 2 (29th November 2018) - Hatton, Fiona L.; Park, Albert M.; Zhang, Yiren; Fuchs, Gregory D.; Ober, Christopher K.; Armes, Steven P.
Abstract : The one-pot synthesis of highly anisotropic epoxy-functional diblock copolymer worms is achieved directly in water using a single monomer (glycidyl methacrylate). Abstract : Nitroxide-functional polymers have garnered considerable interest in recent years and appear to hold promise for energy storage applications. However, their synthesis can be both expensive and time-consuming. Here, we propose a highly convenient method for the preparation of TEMPO-functional diblock copolymer nanoparticles directly in water. Epoxy-functional diblock copolymer worms are synthesized from a single monomer, glycidyl methacrylate (GlyMA), using a three-step, one-pot protocol in aqueous solution via polymerization-induced self-assembly (PISA). First, an initial aqueous emulsion of GlyMA was heated at 85 °C for 9 h to afford an aqueous solution of glycerol monomethacrylate (GMA). Then reversible addition–fragmentation chain transfer (RAFT) polymerization of GMA was conducted in aqueous solution using a dicarboxylic acid-based RAFT agent to produce a water-soluble PGMA homopolymer. Finally, chain extension of this precursor block via RAFT aqueous emulsion polymerization of GlyMA at 50 °C produced amphiphilic diblock copolymer chains that self-assembled in situ to form a 15% w/w aqueous dispersion of diblock copolymer worms. These worms can be derivatized directly using 4-amino-TEMPO in aqueous solution, affording novel crosslinked anisotropic nanoparticles that contain a relatively high density of stable nitroxide radicals for potential charge storage applications.